Innovative visible light-activated sulfur doped TiO2 films for water treatment - Han, C.; Pelaez, M.; V. Likodimos; A. G. Kontos; P. Falaras; O'Shea, K.; Dionysiou, D.D. (Applied Catalysis B: Environmental, 2011)
Visible light-activated sulfur doped TiO2 nanocrystalline films were synthesized by a sol-gel method based on the self-assembly technique with nonionic surfactant to control nanostructure and an inorganic sulfur source (i.e., H2SO4). The films were characterized by UV-vis diffuse reflectance, XRD, TEM, Raman, AFM, ESEM, XPS, FT-IR, EDX, EPR and porosimetry. The results showed that the physicochemical properties of the films, such as BET surface area, porosity, crystallite size and pore size distribution could be controlled by the calcination temperature. The highest surface area, smallest crystallite size and narrow pore size distribution were obtained for sulfur doped TiO2 films calcined at 350°C, which exhibit very smooth surface with minimal roughness (<1nm). The optical absorption edge of sulfur doped TiO2 was red shifted with indirect bandgap energy of 2.94eV. Sulfur species distributed uniformly throughout the films were identified both as S2- ions related to anionic substitutional doping of TiO2 as well as S6+/S4+ cations, attributed mainly to the presence of surface sulfate groups. EPR measurements revealed a sharp signal at g=2.004, whose intensity correlated with the sulfur content and most importantly was markedly enhanced under visible light irradiation, implying the formation of localized energy states in the TiO2 band gap due to anion doping and/or oxygen vacancies. In terms of photocatalytic activity, films calcined at 350°C were the most effective for the degradation of hepatotoxin microcystin-LR (MC-LR) under visible light irradiation, while films calcined at 400°C and 500°C degraded MC-LR to a lower extent, following the evolution of the sulfur content with calcination temperature. The photocatalytic activity of the sulfur doped TiO2 film was stable during three consecutive experiments under visible light irradiation, confirming the mechanical stability and reusability of the doped nanostructured thin film photocatalysts. © 2011 Elsevier B.V.
cited By 272